Control of UHF energy absorption process by resonance method in a shielded object - Dovbnya, A.N.; Yefimov, V.P.; Kramskoy, G.D.; Abyzov, A.S. (Вопросы атомной науки и техники, 2015)
A research program has been developed to account for effect of transverse electric and magnetic fields on a biological object, reaction control of its dielectric constant change, quality factor and heat loss in UHF range in a rectangular resonator in the resonance absorption mode. Розроблено програму дослідження впливу поперечних електричного та магнітного полів на біологічний об'єкт і контролю реакції зміни його діелектричної проникності, добротності й теплових втрат у дециметровому діапазоні довжин хвиль прямокутним резонатором у режимі резонансного поглинання. Разработана программа исследования влияния поперечных электрического и магнитного полей на биологический объект и контроля реакции изменения его диэлектрической проницаемости, добротности и тепловых потерь в дециметровом диапазоне длин волн прямоугольным резонатором в режиме резонансного поглощения.